The Characteristics of Responses to Smart City Device Usage, Maqasid Shariah (The Objective of Shariah) Perspective: The Case of Kota Depok, West Java, Indonesia - Dodik Siswantoro (IQTISHADIA, 2019)
The research aims to analyze the characteristics of smart city device usage from maqasid shariah perspective. The smart city device was developed to support users to fulfill their needs which actually relates to maqasid shariah. Therefore, the higher rate of smart city device usage will increase the quality of life. This includes such factors that make people use this device. This research employs the quantitative method based on the questionnaires distributed to the people of Kota Depok, Indonesia. This device is supposed to increase the activity level of smart city. In fact, only few people use smart city device for their needs and purposes. The benefit of the device is a significant factor to use the smart city device. In addition, not all maqasid shariah aspects covered in the smart city device of Kota Depok.